Seumapa Islamic Art Values in The Wedding Ceremony Process in Aceh - Novysa Basri; Alfi Syahrin; fauziatul Halim; Muhammad Ridha (Catharsis, 2023)
The aim of this research is to examine the values ​​of Islamic art in the wedding ceremony process in Aceh. This research uses a qualitative descriptive method, data collection techniques using observation, interview and documentation stages with the aim of examining the religious values ​​contained in society in Aceh. The results of the research show that the messages conveyed through Seumapa art include poetry, namely when the Seumapa poet recites poetry and the poetry that is sung gives advice to the people of Aceh about the rules of Allah SWT and relationships with society. From the poetry that the poet sings, the opening greeting to the ending of a similar art. Such art has values, namely aesthetic, ethical and spiritual and almost all the poetry sung by dancers gives a message, the message conveyed is related to aqidah, mumalah and morals in aesthetic, ethical and spiritual values. The aesthetic value of the seumapa has a unique poem for the bride and groom as well as a typical chant of the poem with a typical Acehnese twist which is sung in a swinging tone. The ethical values ​​contained in art, such as living in a household, must be honest with each other, not fulfilling bad desires, and also relating to people with mutual respect and always maintaining friendship. Spiritual values, especially relationships with God and humans. Regarding the relationship with Allah, namely the way of life in a household, there must be knowledge of the Islamic religion, for men and women there are procedures for choosing a potential life partner in accordance with the teachings of the Islamic religion or Shari'a, as a man you must be able to recite the Koran correctly and do not miss prayer. and prayers. It is hoped that this research will be able to instill these values ​​in future generations and continue to be preserved.